Changes of Vestibular Symptoms in Menière's Disease After Triple Semicircular Canal Occlusion: A Long-Term Follow-Up Study - Jiang, Yumeng; Xu, Maoxiang; Yao, Qingxiu; Li, Zhuangzhuang; Wu, Yaqin; Chen, Zhengnong; Yu, Dongzhen; Shi, Haibo; Yin, Shankai (Frontiers in Neurology, 2022)
Background: The clinical efficacy of triple semicircular canal occlusion (TSCO) and vestibular nerve resection (VNS) for patients with Ménière’s disease is unclear. Objective: To explore changes in vestibular symptoms after TSCO and its advantages compared to the classical operation of VNS in patients with Ménière’s disease. Methods: In total, 36 patients with Ménière’s disease were enrolled at Shanghai Jiao Tong University Affiliated Sixth People's Hospital, China from May 2005 to July 2021; 12 of them underwent TSCO, 23 underwent VNS, and 1 had both treatments. We compared the demographic parameters, clinical symptoms, and selected test results between the two surgical methods. Ten patients each who underwent TSCO and VNS completed the follow-up; we collected and compared data pertaining to changes in vestibular symptoms. Results: No significant difference in demographic parameters, clinical symptoms, or auditory or vestibular test results was detected between the two groups preoperatively. The TSCO group with vertigo as the main complaint experienced less residual paroxysmal dizziness after surgery than the VNS group (P = 0.020). Also, 57% of the patients in the VNS group had balance disorders after surgery while no such problems were reported in the TSCO group (P = 0.025). Conclusions: Our study shows that TSCO controls vertigo in most Ménière’s disease patients, and also has the advantage of lower rates of postoperative dizziness and imbalance than VNS. Thus, TSCO can be considered as an effective surgery for refractory Ménière’s disease.